2013
DOI: 10.2298/vsp110223044r
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy and apparent diffusion coefficient in evaluation of solid brain lesions

Abstract: Our study showed that 1H-MRS and apparent diffusion coefficients can help in evaluation and differentiation of solid brain lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…DWI has been applied for the assignment of tumor grades or differentiation of tumors, as well as for the diagnosis of ischemic stroke [5,[10][11][12][13][14][15][16]19]. Several investigators found an inverse correlation between the ADC calculated from DW images and tumor cellularity [5,[13][14]16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI has been applied for the assignment of tumor grades or differentiation of tumors, as well as for the diagnosis of ischemic stroke [5,[10][11][12][13][14][15][16]19]. Several investigators found an inverse correlation between the ADC calculated from DW images and tumor cellularity [5,[13][14]16].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some authors reported that the combination of DWI (ADCmin) and MRP (rCBVmax) could be more effective in the differential diagnosis of cerebral tumors [12,18]. The combination of ADC values and MRS findings could be more useful in staging and differential diagnosis of cerebral tumors [5,19]. Additionally, the combination of rCBV and metabolite ratios should be used in differentiating neoplastic-nonneoplastic brain lesions and in grading cerebral gliomas [3,[6][7]9].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Yin et al 16 showed that the ADC values were inversely correlated to the degree of malignancy of gliomas, namely that high grade gliomas had significantly lower ADC and relative ADC (rADC) values in relation to gliomas categorized as low grade. Also, Ristić-Baloš et al 17 reported that DWI can be useful in differentiating benign and malignant tumors from normal parenchyma and in grading gliomas. The results of our research correspond with previous findings from the literature that glial tumors grade II and grade III showed a statistical significance.…”
Section: Discussionmentioning
confidence: 99%